Tracheal stenosis as a late complication of cardiac arrest- a case report - Topyła, Weronika Sandra; Bąk, Tomasz Krzysztof; Krasuska, Beata; Bal, Wioletta Anna; Staciwa, Agnieszka Zofia; Trojnar, Michał (Journal of Education, Health and Sport, 2018)
A sudden cardiac arrest (SCA) and cardiopulmonary resuscitation (CPR) could be associated with numerous acute complications, including rib fractures, sternal fractures, bleeding in the anterior mediastinum. Some of late complications are associated with mechanical ventilation. They include: stenosis, tracheomalacia or tracheoinnominate-artery fistula. These complications can be subclinical or may present as failure to wean from the ventilator, failure to decannulate, or may manifest as upper-airway obstruction with respiratory failure.